Internet Addiction in Constipated Adolescents - Çakar, Sevim; Eren, Gülin (Turkish Journal of Gastroenterology, 2023)
Background: This study aims to assess internet addiction among adolescents with functional constipation and its relationship with sociodemographic and family factors.Methods: In this case–control study, 57 and 35 adolescents with and without functional constipation, respectively, were recruited. Functional constipation was diagnosed by applying the Rome IV criteria. Previously validated Young’s Internet Addiction Test-Short Form and Parent–Child Internet Addiction Test were completed, and sociodemographic data forms were filled out by all participants.Results: According to the Parent–Child Internet Addiction Test questionnaire, 8.8% (n = 5) of the adolescents with FC suffered from internet addiction, whereas none of the healthy adolescents had internet addiction. The Young’s Internet Addiction Test-Short Form survey reported internet addiction among 19.3% (n = 11) of the constipated adolescents and 17.1% (n = 6) of the healthy peers. The ratio of adolescents with limited symptoms and internet addiction in the functional constipation group was as high as 40.4%, according to Young’s Internet Addiction Test-Short Form, and adolescents with functional constipation accompanied by pathological and problematic internet use was 24.6%, according to Parent–Child Internet Addiction Test. Although there was no significant difference in the internet addiction ratio between functional constipation and controls, our findings indicated that adolescents with functional constipation were suffering from high internet addiction rates.Conclusion: The evaluation of Young’s Internet Addiction Test-Short Form and Parent–Child Internet Addiction Test surveys showed high internet usage problems, 40.4% and 24.6% in adolescents with functional constipation. According to adolescents’ self-assessment, the internet addiction rate is higher but not significantly higher than their healthy peers. Therefore, internet addiction should be considered while treating adolescents with functional constipation, and clinicians should consider the opinions of adolescents besides their parents.Cite this article as: Çakar S, Eren G. Internet addiction in constipated adolescents. Turk J Gastroenterol. 2023;34(3):287-292.